Proceedings of the Second ACM-IEEE International Symposium on Empirical Software Engineering and Measurement 2008
DOI: 10.1145/1414004.1414076
|View full text |Cite
|
Sign up to set email alerts
|

A mapping study on empirical evidence related to the models and forms used in the uml

Abstract: Context: Although the Unified Modeling Language (UML) is now widely used, there is little empirical knowledge about the effectiveness of its different elements. Objectives: To conduct a systematic review of the literature describing empirical studies of this paradigm. Method: We undertook a Mapping Study of the literature, based upon electronic searching of major digital libraries.Results: 33 papers have been identified and classified by topic, form of study involved, and type of publication. Conclusions: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 4 publications
(4 reference statements)
0
22
0
3
Order By: Relevance
“…Their study was closely related to the current case study because three of the mapping studies discussed in their paper are also discussed in this paper ( [33], [34] and the Visualization study referred to in Table 3). The study identified a number of educational benefits of mapping studies:…”
Section: Budgen Et Al Suggest That Benefits Of Performing Mapping Stmentioning
confidence: 88%
See 1 more Smart Citation
“…Their study was closely related to the current case study because three of the mapping studies discussed in their paper are also discussed in this paper ( [33], [34] and the Visualization study referred to in Table 3). The study identified a number of educational benefits of mapping studies:…”
Section: Budgen Et Al Suggest That Benefits Of Performing Mapping Stmentioning
confidence: 88%
“…Budgen et al [9] discussed 6 mapping studies including two of the mapping studies discussed in this paper ( [33], [34]). Their study concentrates on mapping studies that are aimed at mapping empirical studies rather than at mapping the research literature as a Final Draft Published in Information and Software Technology, 2011, 53, pp: 638-651 whole.…”
Section: Related Researchmentioning
confidence: 99%
“…Several mapping studies have been published in software engineering [9], such as on the classification of techniques for test-set generation and selection [10], on software development effort and cost estimation [11], on the use of experimental studies [12], on object-oriented design [13] and the use of patterns [14], on the usage of UML diagrams [15], on the empirical evaluation of software requirements specifications techniques [16], on software product lines [17,18], and on domain-specific languages [19]. These mapping studies vary in the form of analysis and in the number of included publications (between 35 and 400).…”
Section: Related Workmentioning
confidence: 99%
“…Investigating this, we found that most publications on MBSE for Industry 4.0 contribute methods to challenges in digital representation (78 publications), integration (58), and processes (32). Moreover, many publications contribute concepts to digital representation (25) and integration (15). Out of the 347 concerns addressed by the included publications, these five combinations of contribution types and concerns are addressed by 60% of the papers in this corpus.…”
Section: Industry 40 Concerns Addressed With Mbsementioning
confidence: 99%
“…Conforme descrito na Seção 2, somente um conjunto limitado de base de dados foi utilizado, portanto é possível que estudos relevantes não tenham sido incluídos. A coerência do sistema de classificação elaborado pode significar uma ameaça à validade, uma vez que o conhecimento necessário para elaborá-lo muitas vezes é obtido somente ao final da seleção [Pretorius and Budgen 2008].…”
Section: Ameaças à Validadeunclassified